P1162Atrial fibrillation and Cardiac resynchronization therapy - is this combination truly bad?. (18th June 2020) - Graca Rodrigues, T E; Nunes-Ferreira, A; Cunha, N; Santos, R; Aguiar-Ricardo, I; Rigueira, J; Silverio Antonio, P; Pereira, S C; Morais, P; Bernardes, A; Pinto, F J; Sousa, J; et al.
Abstract: Introduction:   Cardiac resynchronization therapy (CRT) significantly reduces mortality and hospitalizations in patients with heart failure and reduced ejection fraction (EF). Atrial fibrillation (AF) is a very common comorbidity in these patients, however,  CRT benefit in AF patients has been controversial. Purpose:   To compare the prognostic impact of CRT in patients (pts) with and without AF. Methods: Prospective, single-center study that included pts undergoing CRT implantsince 2015. Clinical and echocardiographicevaluation were made before CRT implant and between 6-12 months post-implant. Pts with EF elevation ≥10% or LV end-systolic volume (ESV) reduction ≥15% were classified as responders. Patients with EF elevation ≥ 20% or ESV reduction ≥30% were classified as super-responders. All the parameters were compared between patients with and without AF.Prognostic impact of CRT was evaluated by comparing total mortality using the Cox regression and Kaplan-Meier methods. Results: From 2015-2019, 566 CRTs were implanted (26.1% female, 72 ± 10.2 years old, follow-up duration 18.9 ± 15.8 months). From these patients, 166 patients (31%) had AF (73.5% males, mean age 72.2 ± 10.2 years, 37.3% ischemic,  LVEF < 30% in 65.5%). The cardiovascular risk factors and comorbidities were similar in both populations (with and without AF), except for chronic kidney disease which was more frequent in AF pts(28% vs 17%, p = 0.012).  The prevalence of complications and surgical revision were similar in both groups. The CRT response rate was similar in both groups (50% in AF group vs 59.6%, p = NS) as was the super-response rate (22.4% in FA pts vs 31.5%, p = NS). The 4-year survival rate of patients with AF was similar to non-AF (83.7% vs 84.3%).  Conclusion:   Despite the controversy about the efficacy of CRT in AF pts, in our population the long-term survival and CRT response rates were comparable between patients with and without AF.